Analisis Hubungan Surat Masuk terhadap Penerbitan Surat Keluar (SPT dan SPPD Karyawan) di Kantor Bupati Langkat Menggunakan Metode Regresi Linear - Erika Handayani Br Siahaan; Fadila Inka Syahfitri; Rico Pradana Dita; Rizq Alwi Marpaung; Hendra Cipta (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to determine the relationship between the number of incoming letters and outgoing letters in the form of Assignment Letters (SPT) and Official Travel Orders (SPPD). The research employs a quantitative approach using simple linear regression analysis, with data collected through direct observation and official document records. The findings indicate a positive relationship between incoming and outgoing letters; however, the relationship is not statistically significant (p-value = 0.068). The coefficient of determination (R²) is 0.358, meaning that 35.8% of the variation in outgoing letters is influenced by incoming letters, while the rest is affected by other factors. These results underscore the need for stronger administrative management systems to improve bureaucratic efficiency and accountability.